FRI0042 Synovial fibroblasts from patients with rheumatoid arthritis differentiate into distinct fibroblast subsets in the presence of cartilage. (23rd January 2014) - Croft, A.; Naylor, A.; Zimmermann, B.; Jaurez, M.; Hardie, D.; Desanti, G.; Filer, A.; Ulf Muller-Ladner, U.; Neuman, E.; Buckley, C.
Abstract : Background: Synovial fibroblasts (SF) are key cellular mediators of joint inflammation and destruction in rheumatoid arthritis (RA). RASF have the potential to migrate to distant cartilage sites where they attach, invade and degrade articular cartilage. Objectives: Using novel markers of SF subsets to identify lining and sub-ling layer SF we investigated the ability of RASF to undergo self-assembly, transmigration and cartilage degradation in vivo . Methods: Healthy human cartilage was co-implanted subcutaneously into SCID mice together with RASF. At the contralateral flank, cartilage was implanted without cells. After 60 days, implants and blood were removed and analyzed. For the detection of human cells, immunohistocytochemistry was performed with species-specific antibodies. For in vitro studies SF were isolated from patients with established RA and normal healthy controls under defined culture conditions and the expression of phenotypic markers analyzed. Results: RASF at the ipsilateral implant differentiated into distinct fibroblast subsets in the presence of cartilage. Cells proximal to cartilage expressed markers of a lining layer phenotype (GP38, FAP, VCAM-1 and Cadherin-11). These cells attached to, invaded and degraded cartilage. Cells more distal to cartilage expressed sub-lining layer phenotype markers including CD248 and CD90. Cells expressing CD248 and CD90 were never observed in the lining layer (proximal to cartilage) and never invaded cartilage. The development of this stromal architecture was very similar to that observed in vivo in the inflamed synovial membrane. This stromal pattern of distinct lining layer and sub lining layer differentiation was completely recapitulated in the contra-lateral implant that contained only cartilage. In addition, we demonstrate that SF in vitro can be directed towards either a lining layer (GP38, FAP, VCAM-1 and Cadherin-11) or sub-lining layer phenotype (f CD248 and CD90) following treatment with various cytokines. The lining layer, but not sub lining cell phenotype is associated with increased cartilage degradation in vitro . Conclusions: Our observations demonstrate that although RASF have an activated cell phenotype ex-vivo they also display a degree of plasticity with the capacity to differentiate into distinct fibroblast subsets associated with lining and sub-lining layer cell markers both in vitro and in vivo . Differentiation into distinct subsets of fibroblasts occurs locally at the site of engraftment following vascular transmigration and totally recapitulate the lining and sub lining anatomy observed at the site of origin. This plastic cell phenotype is dependent on local factors including proximity to damaged cartilage. The formation of such a pathogenic stromal architecture is required for cartilage destruction by RASF. We propose that cellular therapies targeting RASF specific subsets are a potentially important but unexplored therapeutic approach to reduce inflammation and joint damage in patients with RA. Disclosure of Interest: None Declared